Philippine brittlestars (Echinodermata Ophiuroidea) described by R.Koehler (1922) A corrected and annotated list of type specimens. - Ahearn, Cynthia (Smithsonian Institution, 1992)
Smithsonian contributions to zoology ; no. 537